How useful are clinical details in blunt trauma referrals for computed tomography of the abdomen? - Beviss-Challinor, Kenneth B. (SA J Radiol, 2020)
BACKGROUND: The relevance of clinical data included in blunt trauma referrals for abdominal computed tomography (CT) is not known. OBJECTIVES: To analyse the clinical details provided on free-text request forms for abdominal CT following blunt trauma and assess their association with imaging evidence of intra-abdominal injury. METHOD: A single-institution, retrospective study of abdominal CT scans was performed for blunt trauma between 01 January and 31 March 2018. Computed tomography request forms were reviewed with their corresponding CT images. Clinical details provided and scan findings were captured systematically. The relationship between individual clinical features and CT evidence of abdominal injury was tested using one-way cross tabulation and Fisher’s exact test. RESULTS: One hundred thirty-nine studies met inclusion criteria. A wide range of clinical details was communicated. Only clinical abdominal examination findings (p = 0.05), macroscopic haematuria (p < 0.01), pelvic fracture or hip dislocation (p = 0.04) and positive focused assessment with sonography in trauma (p < 0.01) demonstrated an associated trend with abdominal injury. CONCLUSION: Key abdominal examination and basic imaging findings remain essential clinical details for the appropriate evaluation of CT abdomen requests in the setting of blunt trauma. Methods to improve consistent communication of relevant clinical details are likely to be of value.